The application of measures against avoidable harm in Brazilian Health Services: A strategy focusing on patient safety (International Seven Journal of Multidisciplinary, 2024)
The study is the development of a qualitative integrative review, which addresses questions about patient safety with an emphasis on the nuances that permeate the proposals of the praxis of the professional who works in health care and the correlation with common practices and the possibility of reducing possibly avoidable damage. The study's main objective is to find out about the tools used to eliminate avoidable harm to patients in Brazilian health services. The methodology used consisted of an integrative review with a qualitative approach that analyzed studies on the subject published over a 5-year period (2018-2023). The results found were that nursing plays a leading role in the development of actions to prevent the onset of damage compared to other team members, and that there is a need for ongoing education strategies to share knowledge and provide continuity in comprehensive user care. It is therefore necessary to strengthen reporting tools in order to understand the overall picture and create strategies to reduce the potential for harm to occur, as well as proposing health education strategies at all hierarchical levels for professionals who work directly or indirectly in patient care.